ANALISIS PORTOFOLIO SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI SAHAM YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) (Studi pengunaan Model Indeks Tunggal pada saham yang terdaftar di LQ45 Periode Februari 2014 s.d Juni 2015 ) - astawinetu, erwin dyah; fitriyah, lailatul (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRACTThis study aims to determine the optimal shares listed on the Indonesia Stock Exchange  (IDX)  contained  in  LQ45  using the  method  of  single  index model.  This  research  is  a  descriptive  study,  the  method  used  is  quantitative method.  Samples were  taken at thirty-six  shares of the company from  LQ45 period February 2014 to June 2015. The samples were taken using purposive sampling technique. Results from this research that showed that out of thirty-six stock companies only two shares optimal namely PT. Gudang Garam Tbk. (GGRM) and PT. AKR Corporindo Tbk. (AKRA). With the proportion of funds PT. Gudang Garam Tbk. (GGRM) of 0.6624, while PT PT. AKR Corporindo Tbk. (AKRA)  of  0.3376.  In  addition  the  rate  of  return  from  the  formation  of  the portfolio is equal to 0.0084 at the risk of the portfolio amounted to 0.000017 smaller   than   market   risk   amounted   to   0.001404.   This   proves   that   the establishment of a portfolio would gain optimal benefit with certain risk. Keywords: Optimal Portfolio, Single Index Model, risk, rate of return.